Successful talent development in popular game sports in Switzerland: The case of ice hockey. Issue 3 (June 2021) - Stegmann, Pascal; Sieghartsleitner, Roland; Zuber, Claudia; Zibung, Marc; Lenze, Lars; Conzelmann, Achim
There is continuing discussion in talent research on the best approach to developing sporting expertise through learning activities during early sport participation. Among other concepts, the specialized sampling model describes a pathway between early specialization and early sampling and yields promising results in Swiss football. As successful constellations of early sport participation might be affected by sport-specific constraints (e.g., age of peak performance, selection pressure, and physiological/psychological requirements), other popular game sports may show similar promising pathways. This study investigates whether ice hockey, another popular game sport in Switzerland, shows similar successful constellations of early sport participation. A sample of 98 former Swiss junior national team players born between 1984 and 1994 reported on early sport participation through a retrospective questionnaire. Using the person-oriented Linking of Clusters after removal of a Residue (LICUR) method, volumes of in-club practice, free play, and activities besides ice hockey until 12 years of age were analyzed, along with player's age at initial club participation. The results indicate that ice hockey enthusiasts with the most free play and above-average in-club practice had a greater chance of reaching professional level compared to other groups. This implies that high domain specificity with varied sampling experiences is the most promising approach to developing sporting expertise in ice hockey. As similar results were previously found in Swiss football, comparable sport-specific constraints might indeed require similar constellations of learning activities during early sport participation. Therefore, in popular game sports in Switzerland, the specialized sampling model seems to be most promising.